STUDENT'S LEARNING STYLES AND STRATEGIES IN MASTERING THE ENGLISH LANGUAGE : A CLASSROOM BASED RESEARCH IN SMA NEGERI SIWALIMA - Dian Sartin Tiwery; Petra Pratama Ritiauw (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2022)
Abstract : Learning styles are placed as the important role for students and it is the key to students success in learning. Therefore, students really need to recognize their learning styles that are appropriate to themselves to figure out their learning strategies that lead them to their learning objectives that can be effectively achieved. This study is aimed at describing; 1) the learning styles on XI grade students at SMA Negeri Siwalima , 2) the learning strategies of XI grade students at SMA Negeri Siwalima, and 3) the impact of students’ learning styles and their learning strategies in mastering English language of XI grade students at SMA Negeri Siwalima. Descriptive qualitative study design which is supported with visual essay was used to conduct the data. 28 students were involved as the participants of the study Some instruments were applied namely classroom observation, field notes, in-depth interview and review documents to collect the data and it was analyzed by using triangulation method. The results of the study show that (1) the learning styles of XI grade students at SMA Negeri Siwalima are visual learners, auditory learners and kinesthetic learners. Most students have learning styles as Kinesthetic learners (15 students), follow by auditory learners (10 students) and visual learners (3 students). The purpose of using learning styles is to find the best ways for both students to learn effectively and teachers to teach efficiently. (2) The students use varied learning strategies based on their learning styles. Each learning styles has different learning strategies as well as the strengths and weaknesses. (3) There are close relationship between students’ learning styles, their learning strategies and their learning achievement particularly in mastering English language. The more the students know about their learning styles and learning strategies, the better they will have improvement in mastering English language.